Infants born with critical CHD in Arizona and capacities of birth centres for screening and management*. (11th October 2017) - Villa, Lydia; Bjornsen, Brent; Giacone, Heather; Weidler, Erica M.; Bajaj, Ekta; Muth, Andrew; Kennedy, Melanie; Flood, Timothy; Contreras, Dianna; Spadafino, Joseph; Shah, Ashish
Abstract: Objectives: The aims of this study were to identify locations of births in Arizona with critical CHD, as well as to assess the current use of pulse-oximetry screening and capacities of birth centres to manage a positive screen. Study design: Infants (n=487) with a potentially critical CHD were identified from the Arizona Department of Health Services from 2012 and 2013; charts were retrospectively reviewed. Diagnosis was confirmed using echocardiographies. ArcGIS was used to generate maps to visualise the location of treating facility and mother's residence. Birth centres were surveyed to assess screening practices and capacities to manage critical CHD in 2015. Results: Of the 272 patients identified with critical CHD, 52% had been diagnosed prenatally. Patients travelled an average distance of 55.1 miles to their treating facility. Mortality was not related to prenatal diagnosis (p=0.30), living at a high elevation (p=0.82), or to distance travelled to the treating facility (p=0.68). Of 50 birth centres, 33 responded to the survey and all centres practiced critical CHD screening. A total of 25 centres could perform paediatric echocardiographies; 64% of these centres could digitally transmit echocardiograms. In all, 24 birth centres maintained access to prostaglandins. Conclusions: Pulse-oximetry screening in newborns is currently implemented in the majority of Arizona hospitals. Although most centres could perform initial management steps following a positive screen, access to paediatric cardiology services was limited. Patients with critical CHD sometimes travelled a great distance to treating facilities. Digital transmission of echocardiograms or tele-echocardiography would reduce the distance travelled for the management of a positive screen, decrease the financial burden of transportation, and expedite care for critically ill neonates.